Mamantai Kambiang Tradition in Wedding Events in Nagari Silantai Kecamatan Sumpur Kudus Kabupaten Sijunjung Provinsi Sumatera Barat - Tesia, Tesia Anggraini Melcan; Suharti; Emzia Fajri (Kirana Publisher (KNPub), 2023)
This thesis is entitled “The Mamantai Kambiang Tradition in Weddings at Nagari Silantai, Kecamatan Sumpur Kudus, Kabupaten Sijunjung, Provinsi Sumatera Barat”. The mamantai kambiang tradition is a tradition that has existed since ancient times. When the ancient ancestors were still around, but the tradition is still valid and carried out until now. The purpose of this study is to describe the procession of the mamantai kambiang tradition at a wedding in Nagari Silantai. The theory used in this thesis is the theory of symbolic interpretive by Clifford Geertz. This study uses qualitative methods with data collection techniques, namely observation, interviews and documentation. In the procession of the Mamantai Kambiang tradition, there are 2 prisonerts that have just been carried out, namely (preparation and holding), and mamanggigh (calling/ inviting). And in the implementation taban there are also several sections, namely, mamantai kambiang, cooking. Cooking, aka ukah, wine from bako house, sitting in mananti marapulai, and arak ka bako house. The meaning of the tradition of mamantai kambiang for the Nagari Silantai, mamantai kambiang symbolizes the meaning of an award, which is because it uses a goat that has four legs, why does it have to have four legs, because apart from animals that most valuable at that time in Nagari Silantai. In addition, the body part of the kambiang is most needed is the head, which is a form of respect. Some of the meanings of the kambiang head and the meaning of diamond and sipuluik food in the mamantai kambiang tradition.